Age estimation using post-mortem computed tomography and fetal dental radiographic findings in an early to mid-pregnancy fetus: A case report. (May 2023) - Oka, Hiroko; Asao, Yuria; Ohbayashi, Nami; Nakao, Naoki; Ishiuchi, Naoki; Fukumoto, Wataru; Matsumoto, Yoriaki; Kakimoto, Naoya; Nagao, Masataka; Kozai, Katsuyuki
Highlights: There is little dental radiographic information available concerning fetal growth. Calcification of fetal deciduous central incisors is a beneficial indicator for estimating gestational age > 14 weeks. Collaboration between forensic and pediatric professionals is essential for the age estimation of children and fetuses. Abstract: Parameters for body size growth are essential to evaluate the relationship between fetal growth and accurate age estimation in forensics. Size values measured postmortem are also affected by the postmortem environment. On the contrary, when using hard tissue maturation criteria, age estimation remains unaffected by the degree of fetal preservation. In Japan, a fetus dying 12 weeks after pregnancy must be reported as a stillbirth. A Japanese stillborn infant buried without reporting to the authorities underwent a forensic autopsy. The gestational age was 4–5 months, based on the mother's description. The body was not fixed, and it was macerated and flattened along the sagittal plane; therefore it was difficult to correctly measure indicators involving soft tissue. The bone size and tooth development were evaluated using postmortem computed tomography (CT) images and intraoral radiography to estimate the age. Considering all the information, including age estimation based on bone sizes referenced in a Japanese study, calcified upper central incisors, we estimated fetal gestational age for our sample as 14–17 gestational weeks finally. However, there were discrepancies between age estimations based on bone size (20–25 gestational weeks, bone radiographic imaging standards; or 4–6 gestational months, an average of the extremity-bones by a Japanese study) and tooth development (14–17 gestational weeks). Deep discussions based on multiple indices with professionals should be applied to forensic age estimation since existing methods may be based on data for different races, use other measurement tools, or apply different sample conditions even if the targets are the same.